Evaluating The Impact of FDI and Copper Mining in Chile - Muntala, Jonathan A. Kabal (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2023)
This thesis seeks to examine the effects of foreign direct investment (FDI) on Chile's copper industry. Copper production and exports are dominated by Chile on a global scale and demand for copper is increasing due to its critical role in industries such as construction, manufacturing, automotive, and telecommunications. Chile has experienced significant political and economic transformations over the last five decades. Beginning in the 1930s, socialist governments-imposed policies of nationalization and control over key sectors such as copper production and other industries such as banking, finance, and textiles. Under August Pinochet’s dictatorship, the country implemented a series of neoliberal reforms in 1973, including trade liberalization, financial liberalization, and privatization. These changes made it possible for Chile to attract FDI, which was critical to the country's economic development. This research will look at the effects of FDI and copper price on the Chilean economy, using GDP to measure economic growth. The study will employ time-series econometric techniques such as unit root tests, and autoregressive distributed lag model. The study's data will be gathered from 1980 to 2019, spanning a period of significant change in Chile's political and economic policies. The findings of this study will shed light on the relationship between FDI, copper price, and Chilean economic growth. This study also aims to contribute to the broad knowledge of the impact of FDI on the Chilean economy and copper sector.

ÖZ: Bu tez, doğrudan yabancı yatırımın (FDI) Şili'nin bakır endüstrisi üzerindeki etkilerini incelemeyi amaçlamaktadır. Bakır üretimi ve ihracatı küresel ölçekte Şili'de hakimdir ve inşaat, imalat, otomotiv ve telekomünikasyon gibi sektörlerdeki kritik rolü nedeniyle bakır talebi artmaktadır. Şili, son 50 yılda önemli siyasi ve ekonomik dönüşümler yaşadı. 1930'lardan başlayarak, sosyalist hükümetler, bakır fiyatı gibi kilit sektörler ve bankacılık, finans ve tekstil gibi diğer endüstriler üzerinde kamulaştırma ve kontrol politikaları dayattı. Ağustos Pinochet'nin diktatörlüğü altında ülke, 1973'te ticaretin serbestleştirilmesi, finansal serbestleşme ve özelleştirme dahil olmak üzere bir dizi neoliberal reform gerçekleştirdi. Bu değişiklikler, Şili'nin ülkenin ekonomik kalkınması için kritik olan DYY'yi çekmesini mümkün kıldı. Bu araştırma, ekonomik büyümeyi ölçmek için GSYİH'yı kullanarak, DYY ve bakır fiyatının Şili ekonomisi üzerindeki etkilerine bakacaktır. Çalışmada birim kök testleri, eşbütünleşme testleri ve hata düzeltme modelleri gibi zaman serisi ekonometrik teknikler kullanılacaktır. Çalışmanın verileri, Şili'nin siyasi ve ekonomik politikalarında önemli değişimlerin yaşandığı bir dönemi kapsayan 1980'den 2019'a kadar toplanacak. Bu çalışmanın bulguları doğrudan yabancı yatırım, bakır fiyatı ve Şili ekonomik büyümesi arasındaki ilişkiye ışık tutacaktır. Bu çalışma ayrıca DYY'nin Şili ekonomisi ve bakır sektörü üzerindeki etkisine ilişkin geniş bilgiye katkıda bulunmayı amaçlamaktadır.
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2023. Supervisor: Prof. Dr. Salih Katırcıoğlu.
Keywords: Thesis Tez; Banking and Finance Department; Foreign Direct Investments--Copper--Copper Mining--Chile; Chile; Neo-liberalism; FDI; Copper; GDP; MNE; NRC; DD